The Role of a Gluten-free Diet in the Management of Celiac Disease and Non-Celiac Gluten Sensitivity: A Comparative Review - Baginska, Weronika; Pawelec, Natalia; Podkościelna, Jaśmina; Kasterka, Natalia; Ryszkowska, Kamila; Krzyżowska, Kinga; Purska, Aleksandra; Perzynska, Jagienka; Załuska, Urszula (Quality in Sport, 2026)
Celiac disease (CD) and non-celiac gluten sensitivity (NCGS) have been a subject of interest in recent years. The CD is a chronic, gluten-dependent disease characterized by small bowel mucosal inflammation and injury and consequent malabsorption in genetically predisposed individuals. NCGS is characterized by the triggering of intestinal and/or extraintestinal symptoms after the consumption of products made with gluten-containing cereals. Gluten-free diet (GFD) is the only treatment to date of both these conditions. The aim of this study is to evaluate the role of GFD as a therapeutic intervention in CD and NCGS. An extensive review of the literature was conducted using electronic databases (PubMed, Gastroenterology Journal, The Lancet Gastroenterology and Hepatology), and textbooks. Although beneficial to many patients, GFD has many limitations, particularly it may lead to nutritional deficiencies and an imbalanced diet. In this review, the scope of these deficiencies was described and possible solutions were proposed.